The implementation of Sewakadharma work culture to improve public service quality in Denpasar City, Indonesia - Ni Putu Tirka Widanti (Otoritas : Jurnal Ilmu Pemerintahan, 2023)
Public service is defined as an activity that serves the necessity of an individual, people, or organization group that has an interest in the organization based on the main requirements and procedures which are determined and intended to fulfill the satisfaction of service recipients. Employee performance management (PM) is frequently marketed as an innovation to improve public sector performance, but it is internationally challenging to execute. The success of service provider organisations (providers) is strongly dependent on the pleasure of the people who receive these services. The Denpasar City government endeavoured to address this issue by introducing the sewakadarma work ethos in the execution of public services. The Sewaka Dharma is a Hindu ideology that prioritises the alignment of one's thoughts, speech, and actions towards the service of promoting harmony among human, natural, and divine values. The objective of this research is to investigate the impact of the sewakadarma work culture on enhancing the standard of public services in Denpasar City. The present study employs descriptive qualitative research methodologies. The results showed that the sewakadarma work culture has been implemented well through the formation of the sewakadarma cadre, the success of the sewakadarma work culture is evidenced by the awards obtained by the Denpasar city government in providing public services.